2018
DOI: 10.13048/jkm.18016
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Clinical Characteristics of Female Patients with Cold Hypersensitivity on Hands and Feet

Abstract: Objectives: This study was aimed to research clinical characteristics of female patients with cold hypersensitivity on the hands and feet compared with non-cold hypersensitivity group. Methods: 134 women patients were collected from 6 Korean medicine hospitals, and divided into 2 groups(cold hypersensitivity group and non-cold hypersensitivity group). This survey was composed of 19 questions related to clinical symptoms of cold hypersensitivity. Results: We found out the differences between 2 groups in 10 ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…Kong et al reported that women aged 19–59 years presenting with CHHF (n = 70) had a weaker and thinner body type and were more vulnerable to fatigue, indigestion, dry mouth, and skin than controls (n = 68) [ 34 ]. In another study limited to women in their 20s, in addition to sensitivity to cold stimulation, the following characteristics were noted in patients presenting with CHHF: sleep disturbance, irregularities in circadian body rhythm, white finger phenomenon, numbness of limbs, and stiffness in hands [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kong et al reported that women aged 19–59 years presenting with CHHF (n = 70) had a weaker and thinner body type and were more vulnerable to fatigue, indigestion, dry mouth, and skin than controls (n = 68) [ 34 ]. In another study limited to women in their 20s, in addition to sensitivity to cold stimulation, the following characteristics were noted in patients presenting with CHHF: sleep disturbance, irregularities in circadian body rhythm, white finger phenomenon, numbness of limbs, and stiffness in hands [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…보통 수족냉증은 네 가지 경우로서 분류를 할 수 있다 6 . 첫째, 실제로 손과 발의 체온이 정상인데 냉증을 느끼는 경우, 둘째, 손과 발의 체온이 낮고, 자각적 냉증을 느끼는 경우, 셋째, 손과 발의 체온 이 낮으나 자각적 냉증을 보이지 않는 경우, 넷째, 손발이 차다는 느낌 이외에 시리거나, 저린 증상을 포함할 수 있다.…”
unclassified
“…
negative effect on quality of life [9]. The study of 334 healthy subjects aged 50 years or elder in Japan showed that proportion of participants with increased sensitivity to cold widely ranged (6.1%-30.8% men, 14.3%-28.3% women) [12].In Eastern Asian populations CHHF occurs in 20%-52% of subjects [13][14][15], and ratio of men to women is 2:3 [16]. In Japan, this condition called "hiesho" is quite common involving over 60% of females, and in the latter stage of pregnancy "hiesho" manifests in about 40% of women, particularly in the advanced maternal age [17,18].
…”
mentioning
confidence: 99%
“…In Eastern Asian populations CHHF occurs in 20%-52% of subjects [13][14][15], and ratio of men to women is 2:3 [16]. In Japan, this condition called "hiesho" is quite common involving over 60% of females, and in the latter stage of pregnancy "hiesho" manifests in about 40% of women, particularly in the advanced maternal age [17,18].…”
mentioning
confidence: 99%